أساليب قياس مخاطر التشغيل وفقا لاتفاق بازل Ii - محريق, عدنان (جامعة الوادي - University of Eloued, 2015)
تهدف من هذه الدراسة إلى التعرف على المخاطر التشغيلية وأنواعها وكذلك المبادئ التي تشكل الإطار العام للإدارة الفعالة ومراقبة المخاطر التشغيلية بعد التقديم الموجز حول مصادر المخاطر التشغيلية ، لكي تستخدمها البنوك والسلطات الرقابية عند تقييمها للممارسات وسياسات إدارة المخاطر التشغيلية ، بالإضافة إلى كيفية احتساب متطلبات رأس المال اللازم لمواجهة هذا النوع من المخاطر حسب متطلبات معيار كفاية رأس المال الصادر عن لجنة بازل لرقابة المصرفية جوان2004 . This study aims to identify operational risks and types, as well as the principles that form the general framework for the effective management and control of operational risks after the presentation summary about operational risk sources, for use by banks and supervisory authorities when evaluating practices and policies of operational risk management, as well as how to calculate the necessary capital requirements to meet the This type of risk capital adequacy requirements. according to standard issued by the Basel Committee on Banking Supervision ,June 2004.
مقال
Keywords: المخاطر التشغيلية، أسلوب المؤشر الأساسي، الأسلوب المعياري، أسلوب القياس المتقدم; operational risks, the basic indicator approach, the standard approach, advanced measurement method.